Trophic transfer of trace elements within and between aquatic and terrestrial food webs in a forested watershed - Cheng, Matthew Long-Hei; Tsui, Martin Tsz-Ki; Monteverde, Matthew R.; Kwon, Sae Yun; Hoang, Tham C. (Frontiers in Environmental Science, 2025)
Global biogeochemical cycling of trace elements is under influences of anthropogenic inputs and climate change, and their trophic transfers within natural food webs are not yet fully characterized. The present study investigated the trophodynamics of four trace elements (essential: copper and zinc, and non-essential: arsenic and cadmium) in a river food web and compared those with an upland forest food web in a semi-remote watershed in northern California, United States. We found empirical evidence of biomagnification for copper, zinc, and cadmium in the lower trophic levels of both aquatic and terrestrial food webs while we showed biodiminution for arsenic in food webs within the river, but not the forest as shown by calculating Trophic Magnification Factor (TMF), a direct and robust approach to explore the biomagnification efficiency of trace elements along the food web. There was a positive intercorrelation between copper, zinc, and cadmium among the food web components, indicating potential common mechanisms in controlling the trophic transfer of these three cationic trace elements in the natural food webs.